Extra-Cellular But Extra-Ordinarily Important for Cells: Apoplastic Reactive Oxygen Species Metabolism - Podgórska, Anna; Burian, Maria; Szal, Bożena (Frontiers in Plant Science, 2017)
Reactive oxygen species (ROS), by their very nature, are highly reactive, and it is no surprise that they can cause damage to organic molecules. In cells, ROS are produced as byproducts of many metabolic reactions, but plants are prepared for this ROS output. Even though extracellular ROS generation constitutes only a minor part of a cell’s total ROS level, this fraction is of extraordinary importance. In an active apoplastic ROS burst, it is mainly the respiratory burst oxidases and peroxidases that are engaged, and defects of these enzymes can affect plant development and stress responses. It must be highlighted that there are also other less well-known enzymatic or non-enzymatic ROS sources. There is a need for ROS detoxification in the apoplast, and almost all cellular antioxidants are present in this space, but the activity of antioxidant enzymes and the concentration of low-mass antioxidants is very low. The low antioxidant efficiency in the apoplast allows ROS to accumulate easily, which is a condition for ROS signaling. Therefore, the apoplastic ROS/antioxidant homeostasis is actively engaged in the reception and reaction to many biotic and abiotic stresses.